2014
DOI: 10.4038/sljog.v36i1.6962
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of rectal analgesia diclofenac sodium for relief of perineal pain following child birth

Abstract: Objectives: To evaluate rectal diclofenac sodium in the relief of perineal pain after trauma during childbirth.Design: A randomized , double blind trial. Setting:The obstetric department (ward 21) , Professorial Unit, Colombo South Teaching Hospital, Kalubowila.Population: Women with an episiotomy or any degree of perineal tears including vestibular tears, which required suturing.Method: Women were randomly allocated to either diclofenac sodium or placebo suppositories (Anusol) , using a random -number table. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…The summary of the pain scores in the first 24 hourspost-repair shows that the overall pain perception in both group of analgesia was in the mild and moderate severity range. This confirmed similar studies which revealed that diclofenac is an effective analgesia for the control of post perineorrhaphy perineal pain [8,13,14] .…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The summary of the pain scores in the first 24 hourspost-repair shows that the overall pain perception in both group of analgesia was in the mild and moderate severity range. This confirmed similar studies which revealed that diclofenac is an effective analgesia for the control of post perineorrhaphy perineal pain [8,13,14] .…”
Section: Discussionsupporting
confidence: 86%
“…Pain scores were significantly lower in diclofenac group (rectal group) when compared to mefenamic acid group (oral group) [9] . Also, another study reported that diclofenac sodium suppositories group were significantly less likely to experience pain within 24 hours of delivery (percentage of mean pain score reduction, 45%, P < .001) compared with those who received placebo [8] . Nafees et al found that overall pain score was significantly lower immediately and 6 hours after repair in women received diclofenac sodium as rectal suppositories compared to intramuscular injection [13] .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation